A Pilot Quality Improvement Project to Reduce Intraoperative MRI Hypothermia in Neurosurgical Patients. Issue 2 (30th March 2022) - Wong, Becky J.; Rama, Asheen; Caruso, Thomas J.; Lee, Charles K.; Wang, Ellen; Chen, Michael
Abstract : Introduction: Intraoperative hypothermia increases patient morbidity, including bleeding and infection risk. Neurosurgical intraoperative magnetic resonance imaging (iMRI) can lead to hypothermia from patient exposure and low ambient temperature in the MRI suite. This quality improvement project aimed to reduce the risk of hypothermia during pediatric neurosurgery laser ablation procedures with iMRI. The primary aim was to increase the mean lowest core temperature in pediatric patients with epilepsy during iMRI procedures by 1 °C from a baseline mean lowest core temperature of 34.2 ± 1.2 °C within 10 months and sustain for 10 months. Methods: This report is a single-institution quality improvement project from March 2019 to June 2021, with 21 patients treated at a pediatric hospital. After identifying key drivers, temperature-warming interventions were instituted to decrease hypothermia among patients undergoing iMRI during neurosurgery procedures. A multidisciplinary team of physicians, nurses, and MRI technologists convened for huddles before each case. Interventions included prewarmed operating rooms (ORs), blanket coverings, MRI table and room; forced-air blanket warming, temperature monitoring in the OR and iMRI environments; and the MRI fan turned off. Results: Data were analyzed for five patients before and nine patients after the institution of the temperature-warming elements. The sustainment period included 15 patients. The mean lowest intraoperative temperature rose from 34.2 ± 1.3 °C in the preintervention period to 35.5 ± 0.6 °C in sustainment ( P = 0.004). Conclusion: Hybrid OR and MRI procedures increase hypothermia risk, which increases patient morbidity. Implementation of a multidisciplinary, multi-item strategy for patient warming mitigates the risk.